Best Evidence for Each Surgical Step in Minimally Invasive Right Hemicolectomy: A Systematic Review - Alexander A.J. Grüter, MD; Julie M.L. Sijmons, MD; Usha K. Coblijn, MD, PhD; Boudewijn R. Toorenvliet, MD, PhD; Pieter J. Tanis, MD, PhD; Jurriaan B. Tuynman, MD, PhD (Annals of Surgery Open)
Objective:. The aim of this study was to systematically review the literature for each surgical step of the minimally invasive right hemicolectomy (MIRH) for non-locally advanced colon cancer, to define the most optimal procedure with the highest level of evidence. Background:. High variability exists in the way MIRH is performed between surgeons and hospitals, which could affect patients’ postoperative and oncological outcomes. Methods:. A systematic search using PubMed was performed to first identify systematic reviews and meta-analyses, and if there were none then landmark papers and consensus statements were systematically searched for each key step of MIRH. Systematic reviews were assessed using the AMSTAR-2 tool, and selection was based on highest quality followed by year of publication. Results:. Low (less than 12 mmHg) intra-abdominal pressure (IAP) gives higher mean quality of recovery compared to standard IAP. Complete mesocolic excision (CME) is associated with lowest recurrence and highest 5-year overall survival rates, without worsening short-term outcomes. Routine D3 versus D2 lymphadenectomy showed higher LN yield, but more vascular injuries, and no difference in overall and disease-free survival. Intracorporeal anastomosis is associated with better intra- and postoperative outcomes. The Pfannenstiel incision gives the lowest chance of incisional hernias compared to all other extraction sites. Conclusion:. According to the best available evidence, the most optimal MIRH for colon cancer without clinically involved D3 nodes entails at least low IAP, CME with D2 lymphadenectomy, an intracorporeal anastomosis and specimen extraction through a Pfannenstiel incision.